2020
DOI: 10.1108/jbim-02-2020-0095
|View full text |Cite
|
Sign up to set email alerts
|

Buying centre members’ information control and complex organizational buying

Abstract: Purpose This study aims to examine buying center members’ information control (IC) in complex organizational buying contexts to uncover the effect of IC on overall procurement performance (PP) and the effects of expert power (EP), legitimate power (LP) and referent power as antecedents to IC. Design/methodology/approach The study uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Raghavan et al, 2020;Bag et al, 2021;Li et al, 2021;Diba et al, 2019;Fready et al, 2022;Pedersen, 2023). The results lead us to formulate reflections on who holds this information and re-elaborate it to make relevant decisions in terms of suppliers, conditions, times and methods (Prior et al, 2021). First, the use of new technologies has led to improvements in effectiveness, efficiency, cost and time savings and the advantage of data generation, as encapsulated by our P8 (Anin et al, 2020).…”
Section: Discussion and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raghavan et al, 2020;Bag et al, 2021;Li et al, 2021;Diba et al, 2019;Fready et al, 2022;Pedersen, 2023). The results lead us to formulate reflections on who holds this information and re-elaborate it to make relevant decisions in terms of suppliers, conditions, times and methods (Prior et al, 2021). First, the use of new technologies has led to improvements in effectiveness, efficiency, cost and time savings and the advantage of data generation, as encapsulated by our P8 (Anin et al, 2020).…”
Section: Discussion and Contributionsmentioning
confidence: 99%
“…Past research identifies key dimensions, structures and interaction patterns of buying centers, including vertical and lateral involvement, manager centrality and connectedness (Purmonen et al , 2023). Moreover, the B2B purchasing process is described as a complex (Madhavaram et al , 2011; Prior et al , 2021) and evolving (Paesbrugghe et al , 2018) reality that presents itself with great variability in terms of both internal and external situations and factors.…”
Section: Literature Review and Conceptual Backgroundmentioning
confidence: 99%
“…The multi-role/multi-person composition of a BC and its power, politics, interactions, and information controls have for a long time been researched (e.g., reference [74]). However, it is still the subject of recent research that found that information alone is not sufficient; instead, the correct information processing is required (e.g., reference [75]). Still, how "right" information processing is established in a BC is not sufficiently answered, especially if we consider the public sector and the high political influence on procurement decisions.…”
Section: The Link To Procurement Decisions In the Bcmentioning
confidence: 99%
“…The information processing challenges in a BC is the reason why this research links OBB with OIPT theory. In particular, recent research [75] found that the conventional opinion-sharing all information in a BC is a sure-fire way to gain success-is not true. Instead, a measured, deliberate approach seems to be more effective if expert or legitimate power is added.…”
Section: The Link To Procurement Decisions In the Bcmentioning
confidence: 99%
“…First, prior research has largely overlooked B2B encounters – despite their significance for academics and practitioners alike – focusing primarily on business-to-consumer (B2C) markets instead (Baxendale et al , 2015; Kranzbühler et al , 2019). There are specific differences between B2C and B2B transactions, however: for instance, the existence of a buying center, multiple actors and less impact of external factors on business customers (Mora Cortez and Johnston, 2017; Prior et al , 2020). Moreover, if a robust long-term relationship is to be built, business customers will expect solutions and constant interaction (Leek and Christodoulides, 2011; Osmonbekov and Johnston, 2018).…”
Section: Introductionmentioning
confidence: 99%